A Comparative Study of Students’ Perception Towards Quality Assurance Management According to Their Demographics at a University in Bangkok, Thailand - Pang, Yanmei; Ye, Yan (Scholar: Human Sciences, 2021)
The main purpose of this study was to compare the students’ perception towards quality assurance management at a selected university in Bangkok, Thailand. By applying the AUN-QA assessment framework and the theory of total quality management, this study identified students’ perception towards 6 categories: 1) top management commitment, 2) academic staff quality, 3) support staff quality, 4) student advice and support, 5) facility and infrastructure and 6) student focus, compared their perceptions according to 3 pieces of demographics. The results of this study indicated that, the students in the target university held a relatively positive attitude towards quality assurance management. Furthermore, students' most satisfying quality assurance management was student advice and support. The independent sample t-test showed that there was no significant difference of students’ perceptions towards quality assurance management according to students’ gender and nationality, and one-way ANOVA showed that there was no significant difference of students’ perception according to their age. The researcher discussed on the research findings and provided corresponding suggestions to related stakeholders including students, academic staff, support staff, and the top leadership at the selected university in Bangkok, Thailand.